Towards a new emphasis on oral tradition as an information source in African libraries - Alemna, A.A. (Journal of documentation, 1992)
Large numbers of Africans still living in rural areas are considerably influenced by oral tradition. A lot of information can therefore be obtained through this form of communication. However, this kind of material has been largely neglected by librarians in Africa. Although a few centres exist in some countries where the oral tradition is collected, organised and disseminated, a number of obstacles prevent these centres from achieving their aims. The activities of some of these centres are discussed and some of the associated problems highlighted, with proposals made for their solution. The paper concludes that librarians in Africa must place a greater emphasis on oral tradition as a supplement to documentary sources. Oral tradition is an integral part of the African's heritage and it would be criminal to let it disappear.